The role of aversiveness in the relationship between intolerance of uncertainty and inflexible avoidance - Flores Martín, Amanda; López-Gutiérrez, Francisco José; Vervliet, Bram; Cobos-Cano, Pedro Luis (My University, 2018)
The study of avoidance behaviour is considered relevant to improve our understanding of anxiety disorders, which are commonly characterized by the presence of undue avoidance behaviours. Flores et al. (2018) found evidence that Prospective Intolerance of Uncertainty (P-IU) is associated with inflexible avoidance behaviour. Specifically, healthy participants learned in a free-operant discriminative task to avoid an aversive sound, and were tested in extinction to measure the sensitivity of avoidance responses to the devaluation of the sound aversiveness. The results showed that an increase in P-IU was positively associated with insensitivity to outcome devaluation. This association was still significant even when trait anxiety was controlled for. These results suggested that PIU may be a vulnerability factor for inflexible avoidance. However, in a recent replication, we found that the relationship between P-IU and inflexible avoidance was moderated by the participants ratings of outcome aversiveness. Specifically, the significant association between PIU and insensitivity to outcome devaluation was found to be conditional upon high aversiveness ratings.
Keywords: Ansiedad; Avoidance; Intolerance of uncertainty; Outcome devaluation; Outcome aversiveness